2022
DOI: 10.3390/coatings12101435
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of MgO Coating Gd2O3 Nanopowders for Consolidating Gd2O3-MgO Nanocomposite with Homogenous Phase Domain Distribution and High Mid-Infrared Transparency

Abstract: Improved optical and mechanical properties are required for future infrared windows working in harsher mechanical and thermal environments than today. Ameliorating the homogeneity of the phase domain and reducing the size of the phase domain are effective approaches for enhancing the optical transmittance and mechanical hardness of a nanocomposite. In this work, we reported that the Gd2O3-MgO nanopowders were prepared by two different processes. The core–shell nanopowders synthesized by urea precipitation have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Typically, laser ceramics are single-phase and have a cubic crystal lattice to avoid passive optical losses due to scattering [ 3 ]. Recently, it has been shown that it is possible to obtain two-phase Y 2 O 3 -MgO [ 4 , 5 , 6 , 7 ] and Gd 2 O 3 -MgO [ 8 , 9 , 10 ] ceramics with transmission in the wavelength range of 1.5–8 μm at the level of single crystals of rare earth sesquioxides by reducing the grain size to at least a tenth of a wavelength, e.g., 100–200 nm. Such nanocomposites have advantages over sesquioxides in both mechanical properties and thermal conductivity [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Typically, laser ceramics are single-phase and have a cubic crystal lattice to avoid passive optical losses due to scattering [ 3 ]. Recently, it has been shown that it is possible to obtain two-phase Y 2 O 3 -MgO [ 4 , 5 , 6 , 7 ] and Gd 2 O 3 -MgO [ 8 , 9 , 10 ] ceramics with transmission in the wavelength range of 1.5–8 μm at the level of single crystals of rare earth sesquioxides by reducing the grain size to at least a tenth of a wavelength, e.g., 100–200 nm. Such nanocomposites have advantages over sesquioxides in both mechanical properties and thermal conductivity [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Improving the phase domain uniformity and reducing the phase domain size are effective ways to increase the transmittance and mechanical hardness of nanocomposites. The Gd 2 O 3 -MgO nano-powders produced via the urea precipitation method have good transmittance and high Vickers hardness in the mid-infrared band of 3-6 µm, mainly attributed to the uniform distribution of phase domains [18]. Moreover, the Special Issue includes two papers discussing microwave absorbing materials.…”
mentioning
confidence: 99%